Analytical Investigation of the Load-Bearing Behavior of Light Weight Hollow Core Composite Slabs* - et. al., Razan Alzein, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Slabs are considered the most important structural member but also the heaviest one. Therefore, in the last few years a new type of slabs was introduced, hollow core slabs with steel decks. On the other hand, the use of light weight concrete that has got a density less than (1850 kg/m3 ) reduces the self-weight of structures considerably. This paper conducts an analytical study of the ﬂexural behavior of ﬁve slabs, a solid slab that acts as a reference, a hollow core slab with elliptical voids, a composite slab and two hollow core composite slabs using normal weight and light weight concrete using ANSYS software. All the slabs share the same size (2600 x 1200 x 140) mm. The results show that the use of hollow core slabs increases the load carrying capacity by about 32% while using light weight concrete reduces it by about 34% but it also decreases the self- weight and the deformation considerably. The use of light weight hollow core slabs promises with a wide horizon of privileges and improvements in the construction and research domain